"I refused to drink but they still forced me": A mixed-methods approach to understanding the pathways to reduce alcohol use among Vietnamese people with HIV. (May 2022) - Nguyen, M.X.; Hershow, R.B.; Blackburn, N.A.; Bui, Q.X.; Latkin, C.A.; Hutton, H.; Chander, G.; Dowdy, D.; Lancaster, K.E.; Frangakis, C.; Sripaipan, T.; Tran, H.V.; et al.
Abstract: Aims: This study explores the effects of two evidence-based alcohol reduction counseling interventions on readiness to change, alcohol abstinence self-efficacy, social support, and alcohol abstinence stigma among people with HIV (PWH) who have hazardous alcohol use in Vietnam. Methods: PWH receiving antiretroviral therapy (ART) were screened for hazardous drinking and randomized to one of three study arms: combined intervention (CoI), brief intervention (BI), and standard of care (SOC). A quantitative survey was conducted at baseline ( N  = 440) and 3-month post-intervention ( N  = 405), while in-depth interviews were conducted with a subset of BI and CoI participants at baseline ( N  = 14) and 3 months ( N  = 14). Data was collected from March 2016 to August 2017. A concurrent mixed-methods model was used to triangulate quantitative and qualitative data to cross-validate findings. Results: At 3 months, receiving the BI and CoI arms was associated with 2.64 and 3.50 points higher in mean readiness to change scores, respectively, compared to the SOC group (BI: β  = 2.64, 95% CI: 1.17–4.12; CoI: β  = 3.50, 95% CI 2.02–4.98). Mean alcohol abstinence self-efficacy scores were 4.03 and 3.93 points higher among the BI and CoI arm at 3 months, compared to SOC (BI: β  = 4.03, 95% CI: 0.17–7.89; CoI: β  = 3.93, 95% CI: 0.05–7.81). The impacts of the interventions on social support and alcohol abstinence stigma were not significant. Perceived challenges to refusing drinks at social events remained due to strong alcohol abstinence stigma and perceived negative support from family and friends who encouraged participants to drink posed additional barriers to reducing alcohol use. Conclusions: Both the CoI and BI were effective in improving readiness to change and alcohol abstinence self-efficacy among PWH. Yet, participants still faced significant barriers to reducing their drinking due to social influences and pressure to drink. Interventions at different levels addressing social support and alcohol abstinence stigma are warranted. Highlights: Alcohol interventions based on CBT and MET were effective among people with HIV. Readiness to change and alcohol abstinence self-efficacy were improved at 3 months. Participants faced barriers to reducing alcohol use due to social norms. Interventions addressing social support and alcohol abstinence stigma are needed.